2013
DOI: 10.1007/s40519-013-0094-z
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin in eating disorders

Abstract: The potential role that plays adiponectin in the pathogenesis of eating disorders needs to be elucidated by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
0
27
1
1
Order By: Relevance
“…One may argue whether similar central effects exist in humans (Pan et al 2006;Kos et al 2006). Consistent with potential central effects, human adiponectin levels were also shown to be altered in eating disorders such as anorexia nervosa, binge eating disorder and bulimia nervosa (reviewed in, e.g., Bou Khalil and El Hachem 2014). In particular, many studies demonstrated elevated adiponectin serum levels in female patients affected with anorexia nervosa (ModanMoses et al 2007;Pannacciulli et al 2003;Terra et al 2013), while binge eating disorder was related to decreased circulating adiponectin (Monteleone et al 2003;Carnier et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…One may argue whether similar central effects exist in humans (Pan et al 2006;Kos et al 2006). Consistent with potential central effects, human adiponectin levels were also shown to be altered in eating disorders such as anorexia nervosa, binge eating disorder and bulimia nervosa (reviewed in, e.g., Bou Khalil and El Hachem 2014). In particular, many studies demonstrated elevated adiponectin serum levels in female patients affected with anorexia nervosa (ModanMoses et al 2007;Pannacciulli et al 2003;Terra et al 2013), while binge eating disorder was related to decreased circulating adiponectin (Monteleone et al 2003;Carnier et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Research has also shown an association between appetite hormones and eating disorders, specifically binge‐eating disorder (BED) and BN. For example, adiponectin and leptin are appetite‐regulatory hormones that can act as an appetite suppressant that shows associations with both such that adiponectin is decreased in adults with BED and BN, albeit associations with BN are somewhat inconsistent (Khalil & El Hachem, ). On the other hand, leptin is increased in adults with BED and BN (Adami, Campostano, Cella, & Scopinaro, ; Monteleone, Di Lieto, Tortorella, Longobardi, & Maj, ).…”
mentioning
confidence: 99%
“…There are 212 variants within Adipor2 that distinguish the D2J strain from the B6J strain (https://www.sanger.ac.uk), including one 5' UTR SNP, three, 3' UTR SNPs, and over 60 nmd intronic variants (see "high impact variants" in Supplementary Table 1). Serum levels of adiponectin are inversely correlated with BMI and risk for diabetes and are decreased in patients with BED and increased in patients with AN (Khalil and El Hachem 2014).…”
Section: Discussionmentioning
confidence: 99%